The Ecological Scarcity Method for the European Union A Volkswagen Research Initiative: Environmental Assessments - Ahbe, Stephan (AutoUni - Schriftenreihe,, 2018)
This book is published open access under a CC BY 4.0 license. This report transfers the Ecological Scarcity Method (ESM) to the EU and its 28 member states. It provides a powerful tool for unbiased environmental assessments in enterprises and surveys the current impacts and the targets published by environmental authorities, specifically the European Environment Agency. ESM assesses environmental impacts of manufacturing sites and production processes. Developed in 1990 in Switzerland, ESM has already gained regulatory status in proving entitlements for tax exemptions. The method assesses all important impacts in air, water, energy consumption, waste generation and freshwater consumption and also supports en vironmental investment decisions. Contents Methodological Basics Data Research and Results Eco Factors for EU28 Target Groups Practitioners in industries and public authorities in the field of Environment Researchers and students of Ecological Sciences and Industrial Management About the Authors Dr. Stephan Ahbe is initiator and author of Swiss Ecological Scarcity Method published in 1990 and today develops Environmental Management Systems at SYRCON in Darmstadt, Germany. Dr. Simon Weihofen is Environmental and Energy Manager in Group Management at E.ON SE in Essen, Germany. Dr. Steffen Wellge is an Environmental and Energy Management Specialist at the Volkswagen Group Research, Wolfsburg, Germany.